GROWTH AND SURVIVAL OF PACIFIC WHITE SHRIMP Litopenaeus vannamei (BOONE, 1931) IN DIFFERENT SALINITIES - Santos, Carlos Henrique dos Anjos dos (2009)
The aim of this work was to evaluate the development of Litopenaeus vannameiat post-larvae (PL) at different salinities. This experiment was carried out at the “Centro de Tecnologia em Aqüicultura/UFC” at the period from 01/09/2006 to 31/10/2006. Twenty aquariums, with a capacity of 30 liters each one, were randomly distributed in five treatments (control, 0‰, 10‰, 20‰, 30‰ e 35‰) and four replications, at a density of 30 shrimps/aquarium. Initial average total weight and length of PL’s10 were 0.008 ± 0.001 g e 11.00 ± 0.05 mm, respectively. The PL’s were gradually acclimatized at the different experimental salinities. Significant differences among salinity treatments were determined using one-way analysis of variance (ANOVA) followed by least significant difference test of treatment means (Tukey test) (P